Pengaruh Penggunaan Metode Demonstrasi Terhadap Keaktifan Belajar PAK Siswa Kelas VIII SMP Negeri 3 Lintongnihuta, Kabupaten Humbang Hasudutan Tahun Pembelajaran 2023/2024 - Gres Yosefin Sirait; Rusmauli Simbolong; Malani Simanungkalit; Taripar Aripin Samosir; Damayanti Nababan (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2023)
The aim of this research is to determine the effect of the demonstration method on the active learning of PAK class VIII students at SMP N 3 Lintongnihuta, Humbang Hasundutan Regency for the 2023/2024 learning year. The research hypothesis is: